Find $f'(x)$ and $f''(x)$ on the function $f(x) = \displaystyle \frac{1}{x}$ using the definition of a derivative. Then graph $f, f'$ and $f''$ on a common screen and check to see if your answers are reasonable.
Using the definition of derivative
Using the definition of derivative
$
\begin{equation}
\begin{aligned}
\qquad f'(x) =& \lim_{h \to 0} \frac{f(x + h) = f(x)}{h}
&&
\\
\\
\qquad f'(x) =& \lim_{h \to 0} \frac{\displaystyle \frac{1}{x + h} - \frac{1}{x}}{h}
&& \text{Substitute $f(x + h)$ and $f(x)$}
\\
\\
\qquad f'(x) =& \lim_{h \to 0} \frac{x - (x + h)}{(h)(x) (x + h)}
&& \text{Get the LCD on the numerator and simplify}
\\
\\
\qquad f'(x) =& \lim_{h \to 0} \frac{\cancel{x} - \cancel{x} - h}{(h)(x)(x + h)}
&& \text{Combine like terms}
\\
\\
\qquad f'(x) =& \lim_{h \to 0} \frac{-\cancel{h}}{\cancel{(h)} (x)(x + h)}
&& \text{Cancel out like terms}
\\
\\
f'(x) =& \lim_{h \to 0} \left[ \frac{-1}{(x)(x + h)} \right] = \frac{-1}{(x)(x + 0)} = \frac{-1}{(x)(x)}
&& \text{Evaluate the limit}
\\
\\
f'(x) =& \frac{-1}{x^2}
&&
\end{aligned}
\end{equation}
$
Using the 2nd derivative of the definition
$
\begin{equation}
\begin{aligned}
\qquad f''(x) =& \lim_{h \to 0} \frac{f'(x + h) = f'(x)}{h}
&&
\\
\\
\qquad f''(x) =& \lim_{h \to 0} \frac{\displaystyle \frac{-1}{(x + h)^2} - \left( \frac{-1}{x^2} \right)}{h}
&& \text{Substitute } f'(x + h) \text{ and } f'(x)
\\
\\
\qquad f''(x) =& \lim_{h \to 0} \frac{-x^2 + (x + h)^2}{(h)(x^2)(x + h)^2}
&& \text{Get the LCD on the numerator and simplify}
\\
\\
\qquad f''(x) =& \lim_{h \to 0} \frac{-x^2 + x^2 + 2xh + h^2}{(h)(x^2)(x + h)^2}
&& \text{Expand the equation}
\\
\\
\qquad f''(x) =& \lim_{h \to 0} \frac{\cancel{-x^2} + \cancel{x^2} + 2xh + h^2}{(h)(x^2)(x + h)^2}
&& \text{Combine like terms}
\\
\\
\qquad f''(x) =& \lim_{h \to 0} \frac{2xh + h^2}{(h)(x^2)(x + h)^2}
&& \text{Factor the numerator}
\\
\\
\qquad f''(x) =& \lim_{h \to 0} \frac{\cancel{h}(2x + h)}{\cancel{(h)}(x^2)(x + h)^2}
&& \text{Cancel out like terms}
\\
\\
\qquad f''(x) =& \lim_{h \to 0} \left[ \frac{2x + h}{(x^2)(x + h)^2} \right] = \frac{2x + 0}{(x^2)(x + 0)^2} = \frac{2x}{(x^2)(x^2)}
&& \text{Evaluate the limit}
\\
\\
\qquad f''(x) =& \frac{2x}{x^4}
\end{aligned}
\end{equation}
$
Graph $f, f'$ and $f''$
Saturday, September 29, 2018
Single Variable Calculus, Chapter 3, 3.2, Section 3.2, Problem 44
Subscribe to:
Post Comments (Atom)
Why is the fact that the Americans are helping the Russians important?
In the late author Tom Clancy’s first novel, The Hunt for Red October, the assistance rendered to the Russians by the United States is impor...
-
The poem contrasts the nighttime, imaginative world of a child with his daytime, prosaic world. In the first stanza, the child, on going to ...
-
There are a plethora of rules that Jonas and the other citizens must follow. Again, page numbers will vary given the edition of the book tha...
-
The given two points of the exponential function are (2,24) and (3,144). To determine the exponential function y=ab^x plug-in the given x an...
-
Robinson Crusoe, written by Daniel Defoe, is a novel. A novel is a genre defined as a long imaginative work of literature written in prose. ...
-
Hello! This expression is already a sum of two numbers, sin(32) and sin(54). Probably you want or express it as a product, or as an expressi...
-
The title of the book refers to its main character, Mersault. Only a very naive reader could consider that the stranger or the foreigner (an...
-
The only example of simile in "The Lottery"—and a particularly weak one at that—is when Mrs. Hutchinson taps Mrs. Delacroix on the...
No comments:
Post a Comment